2014
DOI: 10.1002/cbin.10328
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin induces cell death in human prostate cancer cell (LNCaP) through survivin protein alteration

Abstract: Calprotectin (CP), an abundant heterodimeric cytosolic protein of neutrophils, conveys a variety of functions such as tumor cell growth arrest and antimicrobial activity. We investigated CP activity and its possible apoptosis-inducing mechanism of action against an antiandrogen therapy-resistance prostate cancer cell line LNCaP. Cell viability and Annexin V FITC assays were performed in order to investigate its cell death activity and apoptosis, respectively. In order to address cell death inducing mechanism(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Consistent with a role in epithelial maturation and renewal, S100A8/A9 induces autophagy and apoptosis (Ghavami et al 2004; Ghavami et al 2008) and significantly increases caspase 3/caspase 7 activity in multiple human cell types (Ghavami et al 2010). In prostate carcinoma cells, calprotectin appears to induce cell death by downregulating the antiapoptotic protein survivin and increasing reactive-oxygen species (Sattari et al 2014). S100A9 alone promoted apoptosis and compromised growth of acute promyelocytic leukemia cells (Zhu et al 2017).…”
Section: Role Of Calprotectin In Cellular Functionsmentioning
confidence: 99%
“…Consistent with a role in epithelial maturation and renewal, S100A8/A9 induces autophagy and apoptosis (Ghavami et al 2004; Ghavami et al 2008) and significantly increases caspase 3/caspase 7 activity in multiple human cell types (Ghavami et al 2010). In prostate carcinoma cells, calprotectin appears to induce cell death by downregulating the antiapoptotic protein survivin and increasing reactive-oxygen species (Sattari et al 2014). S100A9 alone promoted apoptosis and compromised growth of acute promyelocytic leukemia cells (Zhu et al 2017).…”
Section: Role Of Calprotectin In Cellular Functionsmentioning
confidence: 99%
“…Survivin localizes in the mitochondria and inhibits apoptosis. Reports indicate that Survivin protects cancer cells from drug-induced cell death [35]. Many studies indicated that aberrant expression of Survivin is associated with poor prognosis and drug/radiation resistance in breast cancers [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…23 , 24 Previous studies indicated that Survivin could maintain mitochondrial function and protect cancer cell from cell death induced by chemotherapeutic drugs. 25 Survivin expression indicates worse prognosis in patients with bladder cancer. 26 Survivin has also been reported to be crucial for the development of chemoresistance in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%